Composite leading indicator to assess the resilience engineering in occupational health & safety in municipal solid waste management companies. - Rubio-Romero, Juan Carlos; Pardo-Ferreira, María del Carmen; De-la-Varga-Salto, José María; Galindo-Reyes, Fuensanta Carmen (Elsevier, 2018)
Resilience Engineering is a paradigm that attempts to focus on learning from what works well rather than from failures. There have been few studies focusing on the quantitative evaluation of Resilience Engineering and none have been conducted for the Municipal Solid Waste sector. Composite indicators are a useful analytical tool for making decisions involving complex, multi-dimensional social phenomena, and we have used this approach to design a model to assess the level of implementation of Resilience Engineering in Municipal Solid Waste companies. Designed as a Composite Leading Indicator, based on the model created by Wreathall and Shirali et al., its weighting was defined by 22 Spanish and Italian Delphi experts. The results show a high level of consensus. With regard to the principle Top Management Commitment, a high value was assigned to raising awareness over the need to halt production when there is a safety risk. In connection with Culture of Learning, the experts emphasised the importance of establishing mechanisms to clearly define the person responsible for safety in each of the activities carried out in the company. In the area of Flexibility, they agreed on the importance of convincing workers that if they encounter a problem, the criterion to follow is to sacrifice production rather than safety to maintain the system.
Keywords: Ingeniería - Evaluación; Seguridad e higiene laboral; Residuos - Eliminación; Método Delphi; Resilience Engineering; Municipal Solid Waste; Risk prevention; Delphi; Composite leading; Health and Safety; Occupational; Indicators